A Narrative Review with Strategic Analysis of Home Care Services for Older Adults in Seoul, South Korea: Toward a Comprehensive Care Approach - Kim D; Kim H; Hwang R; Jung S; Kim MY; Ko Y; Kang J; Park J; Yun S (Risk Management and Healthcare Policy)
Dasom Kim,1 Hyeongsu Kim,2 Rahil Hwang,3 Sungwon Jung,4 Mi Young Kim,5 Young Ko,6 Jina Kang,7 Jinbeom Park,7 Seoyoung Yun7 1Department of Nursing, College of Health and Medical Sciences, Cheongju University, Cheongju, Republic of Korea; 2Department of Preventive Medicine, School of Medicine, KonKuk University, Seoul, Republic of Korea; 3Department of Nursing, Shinhan University, Uijeongbu-si, Gyeonggi-do, Republic of Korea; 4Department of Nursing, Far East University, Eumseong-gun, Chungcheongbuk-do, Republic of Korea; 5College of Nursing, Hanyang University, Seoul, Republic of Korea; 6College of Nursing, Gachon University, Yeonsu-gu, Incheon, Republic of Korea; 7Expert Group on Health Promotion for Seoul Metropolitan Government, KonKuk University, Seoul, Republic of KoreaCorrespondence: Hyeongsu Kim, Department of Preventive Medicine, School of Medicine, Konkuk University, Annex, 120, Neungdong-ro, Gwangjin-gu, Seoul, 05029, Republic of Korea, Tel + 82-2-2030-7942, Email mubul@kku.ac.krPurpose: This study aimed to establish a role framework and organizational redesign for home care services in response to the evolving internal and external environments in South Korea. The specific objectives were: (1) to perform a Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis based on the external and internal factors related to home care services; (2) to propose key ideas for restructuring services and human resources; and (3) to suggest strategies for enhancing the quality of home-based care services.Patients and Methods: The policy landscape for older adult healthcare in Seoul, South Korea along with the current state and challenges of home care services were reviewed. A systematic analysis of internal and external factors influencing organizational goals and strategies was conducted following the SWOT analysis framework.Results: We highlight the difficulties in grassroots health management and suggest the need for regional organizational structures. A transition from individual nurse-centric care to a team-based approach is suggested with an emphasis on targeting services to vulnerable groups.Conclusion: Restructuring of home care services is essential with a focus on vulnerable populations and the establishment of performance metrics. Seamless communication between stakeholders and specialized training for team leaders are crucial for successful implementation.Keywords: aged, home care services, Korea, health policy, health services research